Food-related attentional bias and its associations with appetitive motivation and body weight: A systematic review and meta-analysis. (1st February 2021) - Hardman, Charlotte A.; Jones, Andrew; Burton, Sam; Duckworth, Jay J.; McGale, Lauren S.; Mead, Bethan R.; Roberts, Carl A.; Field, Matt; Werthmann, Jessica
Abstract: Theoretical models suggest that food-related visual attentional bias (AB) may be related to appetitive motivational states and individual differences in body weight; however, findings in this area are equivocal. We conducted a systematic review and series of meta-analyses to determine if there is a positive association between food-related AB and: (1.) body mass index (BMI) (number of effect sizes ( k ) = 110), (2.) hunger ( k = 98), (3.) subjective craving for food ( k = 35), and (4.) food intake ( k = 44). Food-related AB was robustly associated with craving ( r = 0.134 (95% CI 0.061, 0.208); p < .001), food intake ( r = 0.085 (95% CI 0.038, 0.132); p < .001), and hunger ( r = 0.048 (95% CI 0.016, 0.079); p = .003), but these correlations were small. Food-related AB was unrelated to BMI ( r = 0.008 (95% CI -0.020, 0.035); p = .583) and this result was not moderated by type of food stimuli, method of AB assessment, or the subcomponent of AB that was examined. Furthermore, in a between-groups analysis ( k = 22) which directly compared participants with overweight/obesity to healthy-weight control groups, there was no evidence for an effect of weight status on food-related AB (Hedge's g = 0.104, (95% CI -0.050, 0.258); p = .186). Taken together, these findings suggest that food-related AB is sensitive to changes in the motivational value of food, but is unrelated to individual differences in body weight. Our findings question the traditional view of AB as a trait-like index of preoccupation with food and have implications for novel theoretical perspectives on the role of food AB in appetite control and obesity.